Mode-I Metal-Composite Interface Fracture Testing for Fibre Metal Laminates - Periyasamy Manikandan; Gin Boay Chai (Advances in Materials Science and Engineering)
The main contribution of the present paper is the determination of the mode-I fracture of metal-composite interface region for fibre metal laminates (FMLs). A hybrid DCB configuration is proposed to investigate the mode-I fracture between metal-composite interface using experimental and numerical approaches. A computationally efficient and reliable finite element model was developed to account for the influence of metal plasticity on the measured fracture energy. The results of the experimental and numerical studies showed that metal plasticity increases the fracture energy of the metal-composite interface as the fracture event progresses. The applied energy truly utilized to propagate metal-composite interface fracture was predicted numerically by extracting the elastic strain energy data. The predicted true fracture energy was found to be approximately 50% smaller than the experimentally measured average propagation energy. The study concluded that metal plasticity in hybrid DCB configuration overpredicted the experimentally measured fracture energy, and this can be alleviated through numerical methodology such as the finite element approach as presented in this paper.